Person, Religation, and Moral Reality: Ethical Concepts in the Light of Zubiri’s Anthropology - Fernández, Óscar Barroso (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The article analyzes how Zubiri’s thinking flows into moral philosophy starting from the question about how man makes his life once installed in reality. The first part highlights the role of religation in this regard. For Zubiri, all formulations about man as a moral reality can be taken from religation. The obligation to realize himself in his mediation with reality is imposed on man in being human. But in turn, how to realize himself is not dictated to him; rather, it is something he himself has to determine. The second part analyzes how the consideration of man as animal of realities leads to a vision of man as a constitutive moral reality. This allows for the treatment of the meaning of the principal moral concepts from a formal view point; at the same time, it also allows the confrontation between the formal view point and the formalism of Kantian obligation. Zubiri’s analysis, in so far as it is an analysis of reality in its formality, is also an analysis of the anthropological structures (in their transcendental moment). This permits recuperating the discussion about ethos for moral philosophy, posing liberty in continuity with human tendencies and obligation in continuity with being, and finally, it makes happiness enjoy once more a central place in moral philosophy.